Polycentrisme urbain : une réalité spatialement mesurable ? - Marc Servais; Isabelle Thomas; Haike Van Dyck; Ann Verhetsel (Cybergeo, 2004)
It has already widely been shown that the extension of the urban space takes a polycentric shape: suburban employment sub-centres emerge. The objective in this study is to measure employment concentrations inside and around urban agglomerations and to determine operational tools (methods and data) that lead to the highlighting of these sub-centers. Advantages and limits of the methods are discussed. Our cases studies are Antwerp and Brussels. The results obtained by several methodologies are compared (shift and share analysis, cluster analysis, kernel interpolation and local autocorrelation) for three different types of employment data (social security, population census and regional development statistics) and at three different scales of analysis (individual postal address, neighbourhood and commune). The main difficulties encountered are: (1) the spatial and temporal heterogeneity of the data, and (2) the non-uniqueness of the methodology for discriminating sub-centers. Our conclusion is that there is an emerging polycentric structure in Brussels and Antwerp, but sub-centers are still difficult to put forward. The combination of several different methods and databases is necessary to get insight in the polycentric structure.